GALVEZ Noodle/ Muhammad Yusri Mohd Yusof... [et al.] - Mohd Yusof, Muhammad Yusri; Jahaya, Mohd Firdaus; Mahmor, Azizul Firdaus; Mohd Zain, Mohd Budiman; Salamat, Mohd Alif (2009)
After a few discussions, we have decided the establishment of our business is on laundry services. We choose Galvez Noodle as our company name. Our premise located at No 4, Lorong Pantai Gelebang, Malacca Raya Utama, 75520 Malacca . This location is quite strategic because it’s near to the town and easy to get customers. Galvez Noodle has started on January 2010 and has four managers that have their responsibility at the department and one worker with their responsibility at the office site. We have decided to run this business in the form of partnership because it is easier to set up the business and it required a few risk to run the business based on our competitor. During the first month, a few problems might occur because we are new in this market and we are having a problem with less of customer because in early year there is no specific season. Besides, we might face a few competitors that are running the same business with us. But we try to provide a good service for our customer and give the reasonable price for our customer. Our planning in a second year after we started the business is we will come up with new services and we use an upgrade of equipment that can perform faster and give maximum satisfaction to our customer. We believe that we will succeed although it takes some time. With the good on marketing, we believe that we will able to reach our target and become stabilize in this business. The important thing is all of our customers are satisfied with our services and will accept us in running this business.